Pengaruh Environmental Social dan Governance Disclosure Terhadap Nilai Perusahaan pada Perusahaan Food Product di Asean Periode 2022 – 2023 - Pungky Dwi Asrianingtyas; Sundjoto; Sri Rahayu; Christina Wulansari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of Environmental Social Governance (ESG) disclosure on Company Value in the food product sector in ASEAN during the period 2022-2023. In this study, company value is measured using the Price to Book Value (PBV) ratio, while ESG disclosure consists of three main dimensions, namely Environmental disclosure, Social disclosure and Governance disclosure. This study uses a quantitative approach with a multiple linear regression method. The research sample consisted of 30 food product companies selected using the purposive sampling method, based on certain criteria such as consistent annual report publication and complete ESG disclosure. Research data were obtained from annual reports, sustainability reports, and the Thomsonreuters database. The results of the study show that environmental and governance disclosure have a positive effect on company value, while social disclosure shows a negative effect on company value. Simultaneously, ESG disclosure has a significant effect on company value, supporting stakeholder theory and signal theory which emphasize the importance of transparency and sustainability.